The use and context of the term 'multimorbidity' in rheumatoid arthritis: a systematic literature review. (3rd March 2021) - Dey, Mrinalini; Busby, Amanda; Elwell, Helen; Pratt, Arthur; Young, Adam; Isaacs, John; Nikiphorou, Elena
Abstract: This systematic literature review aimed to analyse terms describing coexisting conditions in the RA literature, informing the need for an operationalized definition of multimorbidity. Articles discussing RA with multimorbidity, published 1946 until August 2020, were identified. The primary outcome was the use and/or definition of 'multimorbidity' in RA. Information extracted included terms defining coexisting conditions, the use of a comorbidity/multimorbidity score and the use of 'index disease' to describe RA (more applicable to comorbidity than multimorbidity). Thirty-nine articles were included. Eight articles used the term 'multimorbidity', 18 used 'comorbidity' and 12 used both terms, 7 synonymously. One used no term. Fourteen articles fully defined the term. The number of co-existing conditions described in included studies was one-121. Twelve articles used a comorbidity/multimorbidity score. Four articles described RA as the 'index disease'. Our results demonstrate inconsistent use of the term multimorbidity. Improved assessment of multimorbidity is indicated in RA patients, including an operationalized use and definition.